Deeper Integration and Trade in Services in the Euro-Mediterranean Region : Southern Dimensions of the European Neighborhood Policy - Müller-Jentsch, Daniel (Washington, DC: World Bank, 2012)
Deeper economic integration with the enlarged European Union - which accounts for a quarter of global GDP and foreign direct investment - could become a main driver for economic development in the southern Mediterranean countries. The planned Euro-Mediterranean free trade area for goods is a first step into that direction, but additional measures are needed. Especially the liberalization of services trade and the comprehensive domestic reforms this entails would strengthen the linkages with global and European markets. This study analyzes the adjustment needs and policy options associated with deeper integration between the two sides of the Mediterranean Sea. It puts specific emphasis on the dynamics of deeper integration at the company level and their respective policy implications. Besides a general discussion of deeper integration and trade in services liberalization, the study contains detailed assessments of individual sectors - especially the backbone services (e.g. transport, telecommunications, financial markets, electricity) and other sectors of relevance for deeper integration (tourism, IT-enabled services, distribution services). Even though the focus is on regional integration, multilateral liberalization issues are factored into the analysis (e.g. the GATS, the WTO Doha Round) and options for the pursuit of an "open regionalism" are explore.